Studies on the Cārvāka/Lokāyata - Bhaṭṭācārya, Rāmakr̥shṇa (Cultural, historical and textual studies of religions., 2011)
This volume is the first attempt at a scientific study of the Carvaka/Lokayata, the materialist system of philosophy that flourished in ancient India between the eighth and the twelfth century CE.